Full compliance with Respiratory syncytial virus prophylaxis was associated with fewer respiratory‐related hospital admissions in preterm children: A cohort study. (6th December 2020) - Torchin, Heloise; Charkaluk, Marie‐Laure; Rousseau, Jessica; Marchand‐Martin, Laetitia; Treluyer, Ludovic; Nuytten, Alexandra; Truffert, Patrick; Jarreau, Pierre‐Henri; Ancel, Pierre‐Yves
Abstract: Aim: Although well documented in randomised trials, the efficacy of prophylaxis against respiratory syncytial virus (RSV) in real‐word conditions is less studied. The objective was to assess the impact of partial versus full RSV prophylaxis for acute respiratory infections (ARIs) and ARI‐related hospital admissions in preterm children. Methods: This study included children born preterm in 2011 in France who were eligible for RSV prophylaxis and received at least one palivizumab dose from October 2011 to March 2012. Full prophylaxis was defined as receiving at least one palivizumab dose for each month of RSV exposure in the community. Children with full and partial prophylaxis were matched, and odds of ARIs and ARI‐related hospital admission were compared by logistic regression. Results: Full prophylaxis concerned 861/1083 (80%) children. As compared with full prophylaxis, partial prophylaxis was not associated with ARI occurrence (odds ratio OR 1.3, 95% confidence interval CI 0.9‐1.9) but was significantly associated with ARI‐related hospital admission during the RSV epidemic (OR 1.9, 95% CI 1.2‐2.9). Conclusion: During the 2011‐2012 RSV epidemic, hospital admission rates were higher for preterm children with partial than full RSV prophylaxis. Improving compliance could help alleviate the burden of RSV on healthcare systems.